2015
DOI: 10.1111/1752-1688.12349
|View full text |Cite
|
Sign up to set email alerts
|

Trust in Sources of Soil and Water Quality Information: Implications for Environmental Outreach and Education

Abstract: Public trust in organizations focused on improving environmental quality is important for increasing awareness and changing behaviors that have water quality implications. Few studies have addressed trust in soil and water quality information sources, particularly for both agricultural and nonagricultural respondents of the same watersheds. Surveys in 19 watersheds across five states in the Midwest assessed trust in, and familiarity with, soil and water quality information sources. Overall, respondents most tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
(92 reference statements)
3
21
0
Order By: Relevance
“…The ultimate success of a non-profit organization relies on its ability to keep promises and act in favor of its supporters' best interests (Kang & Hustved, 2014). The lower levels of trust in for-profit organizations compared to government organizations and non-profit organizations is consistent with some study results (Auger, 2011;Martin et al, 2016;Mase et al, 2015), but not with the results of Ruth (2015), which indicated comparable levels of source credibility between government and for-profit organizations when communicating about genetically modified food.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The ultimate success of a non-profit organization relies on its ability to keep promises and act in favor of its supporters' best interests (Kang & Hustved, 2014). The lower levels of trust in for-profit organizations compared to government organizations and non-profit organizations is consistent with some study results (Auger, 2011;Martin et al, 2016;Mase et al, 2015), but not with the results of Ruth (2015), which indicated comparable levels of source credibility between government and for-profit organizations when communicating about genetically modified food.…”
Section: Discussionsupporting
confidence: 86%
“…For an organization to communicate effectively with the public, trust is a necessary component. (Brewer & Ley, 2013;Lang, 2013;Martin et al, 2016;Mase et al, 2015;Ruth, 2015). If members of the public lack knowledge and rely on trusted organizations to shape their decisions (Brossard & Nisbet, 2007), understanding the public's trust of organizations that communicate about agricultural and natural resources issues is imperative.…”
Section: Why Trust Is Importantmentioning
confidence: 99%
See 2 more Smart Citations
“…Lang (2013) found that environmental non-profits were trusted by the U.S. public more than governmental and for-profit organizations, which had similar levels of public trust. Mase, Babin, Prokopy, and Genskow (2015) assessed Midwesterners' trust for information about soil and water quality, finding Extension was trusted the most, followed by government agencies, non-profit organizations, and for-profit organizations. Martin et al (2016) assessed Coloradoans trust of agricultural and food information from various types of sources and found universities were trusted the most, followed by governmental agencies.…”
Section: Why Trust Is Importantmentioning
confidence: 99%